Change From the Middle: A Grounded Theory Approach on Middle Manager-Initiated Organizational Change From a Southeast Asian Context - Balgos, Marcial Orlando A, Jr (Archīum Ateneo, 2020)
Prior studies on the strategic influencing done by middle managers emphasized on a unidirectional sensemaking and failed to explore how middle managers utilized discursive capabilities in engaging stakeholders in change projects. To forward this, we used the Leader-Member Exchange (LMX) theory as embedded within the power distant cultural norms of Philippine society. Using the LMX model as frame, we aimed to understand how middle managers position and navigate themselves to promote change upward in the organizational hierarchy. Respondents for this study were middle managers in small or mid- sized companies reporting to a business unit with subordinates working under them. Results showed middle managers utilized smooth interpersonal consultative relationships to strategically influence others, and paired this with the financial and output-focused language of their superiors. Communication, negotiation, and persuasion were considered essential leadership skills in working with peers and subordinates, while expectations of responsibility and autonomy helped initiate change. These findings open the discussion for leadership development